Does mind wandering mediate the effects of habitual reading motivation on comprehension?. (February 2023) - Soemer, Alexander; Gericke, Christian; Schiefele, Ulrich
Abstract: The present article reports on a study that examined how individual differences in habitual reading motivation affect a reader's tendency to engage in text-related and text-unrelated thinking during reading. Two-hundred participants read each three texts about finance and meteorology topics and answered comprehension questions afterward. Participants' thoughts during reading were assessed with retrospective ratings and thought samples. Habitual reading motivation was assessed with questionnaires in a separate session prior to reading. Structural equation models fit to this data revealed that more motivated readers reported less mind wandering, more engagement in elaborative thinking and comprehension monitoring, as well as higher topic interest. Furthermore, the beneficial effect of reading motivation on comprehension was partially mediated by mind wandering, elaboration, comprehension monitoring, and interest. Our findings offer a novel explanation for the well-known beneficial effects of reading motivation on comprehension: habitually motivated readers are more likely to engage in text-related thinking and avoid text-unrelated thoughts. Highlights: Habitual reading motivation reduces mind wandering during reading. Habitual reading motivation promotes elaboration and comprehension monitoring. Habitual reading motivation promotes comprehension by reducing mind wandering.